CRITIQUING THE DISCOURSE ON WOMEN IN THE EDO ERA: INTERTEXTUAL STUDIES OF ARIYOSHI’S HANAOKA SEISHŪ NO TSUMA - Ariefa, Nina Alia; Budianta, Melani; Hapsarani, Dhita (UI Scholars Hub, 2023)
Under the Tokugawa clan, Japanese women’s position was declined throughout the Edo era (1603–1868). Almost one century afterwards, a female writer called Ariyoshi Sawako (1931–1984) raised the issue of female position in the Edo era through the novel Hanaoka Seishū no Tsuma (HSNT). This article will focus on two things. First is the exploration of the discourse of women in the Edo Era through three texts written during the era. The second part of the article will discuss the intertextuality of novel, with the discourse on women in the Edo era. New historicism method and Foucault’s concepts of discourse and power will be used to expose the patterns that make up the discourse on women. The article concludes that HSNT opens up various social and cultural issues in the Edo era related to women’s experience as a critique of the controlling discourse on women in the Edo period.